2021
DOI: 10.1111/cei.13589
|View full text |Cite
|
Sign up to set email alerts
|

Spliced HLA-bound peptides: a Black Swan event in immunology

Abstract: Peptides that bind to and are presented on the cell surface by human leucocyte antigen (HLA) molecules play a critical role in adaptive immunity. For a long time it was believed that all the HLA-bound peptides were generated through simple proteolysis of linear sequences of cellular proteins, and therefore are templated in the genome and proteome. However, evidence for untemplated peptide ligands of HLA molecules has accumulated during the last two decades, with a recent global analysis of HLA-bound peptides s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 45 publications
(171 reference statements)
0
17
0
Order By: Relevance
“…Spliced peptides are not peculiar to virus-, alloantigen-or cancer-derived epitopes but are derived from bacterial proteins as well, e.g., Listeria monocytogenesi-a bacterium with an obligatory cytosolic lifestyle [216,217] . Thus, a As several such examples followed (reviewed in [218,219] ), three questions became apparent: one, does splicing occur only in cis-between peptides generated from the same protein as in the three examples above-or can it occur in trans-between peptides generated from two different proteins; two, what fraction of the peptides in a immunopeptidome owes to peptide splicing; and three, can cytokines influence peptide splicing in the proteasomes considering that IFN- induces immunoproteasomes? Answers to these questions have come from deep sequencing of the immunopeptidomes eluted from HLA-I molecules.…”
Section: Peptide Dicing and Splicing Adds To Antigen Diversitymentioning
confidence: 99%
“…Spliced peptides are not peculiar to virus-, alloantigen-or cancer-derived epitopes but are derived from bacterial proteins as well, e.g., Listeria monocytogenesi-a bacterium with an obligatory cytosolic lifestyle [216,217] . Thus, a As several such examples followed (reviewed in [218,219] ), three questions became apparent: one, does splicing occur only in cis-between peptides generated from the same protein as in the three examples above-or can it occur in trans-between peptides generated from two different proteins; two, what fraction of the peptides in a immunopeptidome owes to peptide splicing; and three, can cytokines influence peptide splicing in the proteasomes considering that IFN- induces immunoproteasomes? Answers to these questions have come from deep sequencing of the immunopeptidomes eluted from HLA-I molecules.…”
Section: Peptide Dicing and Splicing Adds To Antigen Diversitymentioning
confidence: 99%
“…However, it is clear that there are still informatic challenges in the peptide-centric data analysis pipelines (12,13) with a much lower proportion of spectra confidently assigned from immunopeptidomics data compared with more conventional samples such as tryptic digests of cell lysates. The search to explain these dark elements of the immunopeptidome has driven differences in interpretation and peptide sequence assignments to these MS/MS spectra (12,(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional wisdom immediately decreed their existence and the proteasomal generation of such spliced peptides as being a rare event. Their presence in several other disease states has recently been reviewed ( 23 , 33 ) but perhaps most surprisingly (and controversially) the frequency of these peptides in the HLA class I immunopeptidome was reported to be up to one third of all peptides identified isolated HLA peptide ligands ( 15 ). This ground-breaking study from Liepe and colleagues ( 15 , 19 ) has been confirmed by some ( 16 ) and disputed by others ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A significant degree of excitement has arisen in the field of MHC peptidome (immunopeptidome) research, with the claim that some MHC-presented peptides derive from peptide splicing ( 3 , 4 , 5 ), as reviewed ( 6 , 7 , 8 , 9 , 10 , 11 , 12 ). This concept has stirred the field tremendously; if indeed, some peptides are spliced before loading onto the MHC, the size of the required protein sequence database used for searching peptide ligands, is many folds larger than the currently used canonical protein sequence database.…”
mentioning
confidence: 99%